QUALITY CHARACTERISTICS OF SMOKED LELE DUMBO FILLET (Clarias gariepinus) WITH BUMBU FORMULATION DIFFERENT - Deli Rosiana Yanti; Syahrul Syahrul; N. Ira Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
Abstrak       This study aims to determine the quality characteristics of the dumbo catfish fillets with different seasoning formulations. The method used in this research was experimental, namely processing the dumbo catfish fillets with different formulations. The research design used was a completely randomized design (CRD), with 3 levels of treatment, namely F1 seasoning formulation (20% brown sugar + 7% white sugar), F2 seasoning formulation (7% white sugar + 20% chili), and F3 seasoning formulation. (brown sugar 20% + chili 7%). The parameters observed were organoleptic, chemical analysis and total bacterial colonies. The results showed that the quality of dumbo catfish fillet jerky with different seasoning formulations had a significant effect on the appearance, aroma, texture, taste, moisture content, ash, protein, fat and total bacterial colony test at the 95% confidence level. Dumbo catfish fillets with different formulations of good quality, namely in the F3 treatment (brown sugar 20% + 7% chilli), with an average value of 7.03, aroma 6.84, texture 6.87, taste 6.39, moisture content 10.21%, content ash 0.46%, protein content 19.41%, and fat content 2.04% with a total bacterial colony of 2.8 x 103 colonies / g.